2013
DOI: 10.1371/journal.pone.0077444
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Age and General Cognitive Ability—A Cross Sectional Study of Danish Male Conscripts

Abstract: ObjectivesOffspring of older men have impaired cognitive ability as children, but it is unclear if this impairment persists into adulthood. The main objective of this study was to explore the association between paternal age at offspring birth and general cognitive ability as young adults.DesignPopulation-based cross-sectional study with prospectively collected data on obstetric factors and parental education.SettingNationwide Danish sample.ParticipantsMale conscripts (n = 169,009).Primary and secondary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
(47 reference statements)
5
10
0
Order By: Relevance
“…The sibling-comparison analysis gave a similar result. This is consistent with two previous studies4546, although two others4449 found least some decline in offspring intelligence among older mothers as well as younger ones. Most of these studies found that associations of maternal and paternal age with offspring intelligence were similar, both before and after adjustment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The sibling-comparison analysis gave a similar result. This is consistent with two previous studies4546, although two others4449 found least some decline in offspring intelligence among older mothers as well as younger ones. Most of these studies found that associations of maternal and paternal age with offspring intelligence were similar, both before and after adjustment.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with most previous studies of offspring intelligence444546, educational achievement121347 and social adjustment48. There is less consistency across studies once adjustment is attempted, due perhaps in part to the different approaches taken.…”
Section: Discussionsupporting
confidence: 88%
“…However, the finding that young maternal age is associated with a lower mean IQ of young adult offspring is consistent with three large studies [3, 15, 45]. McGrath et al[45] using a cross-sectional study (n = 169,009) found that the offspring at age 18 years who born to teenage mothers had a lower mean IQ of -1.69 (95% CI: -2.03 to -1.34) after adjusting for parental age and education, birth order, multiple birth status, birth weight and gestational age. McGrath and colleagues reported offspring of teenage fathers also had a lower IQ (Mean difference -0.69; 95% CI: -1.34, -0.04).…”
Section: Discussionsupporting
confidence: 90%
“…In an effort to avoid or reduce the risk of bias due to confounding factors, we examined whether an independent effect of infections on general cognitive ability could be detected in a model adjusting for other factors known to influence the cognitive ability (e.g. parental education, gestational age, birth weight and birth order) [ 16 ]. Additionally, we explored a possible dose-response relationship, the temporal associations, severity, and the effect of the type and site of the infection.…”
Section: Introductionmentioning
confidence: 99%